Focus Group Discussion Tentang Interprofessional Collaboration dalam upaya pengendalian stunting - Risnah Risnah; Muhammad Irwan; Rosmah Rosmah (Jurnal Pengabdian Kesehatan Komunitas, 2021)
Stunting is one of the national health problems caused by multidimensional factors. Therefore, it requires attention and joint handling. Children who experience stunting increase, the risk of suffering from repeated infections that can result in death such as diarrhea, pneumonia and smallpox. It also increases the risk of developing chronic heart disease in childhood. The activity carried out in this service is Focus Group Discussion (FGD). The target of the activity is health workers, village officials and leaders as well as the community in the working area of the Pamboang Health Center, Majene District, West Sulawesi. The results of the activity showed that health workers already understood matters related to Interprofessional collaboration including supporting and inhibiting factors, so that they were still technically constrained in their implementation. The suggestion is to improve the implementation of Interprofessional collaboration, it is necessary to have a technical module for the implementation of Interprofessional collaboration in dealing with stunting cases in children at the Puskesmas level. ABSTRAK Stunting merupakan salah satu permasalah kesehatan secara nasional yang diakibatkan oleh faktor multidimensi sehingga membutuhkan perhatian dan penanganan bersama. Anak-anak yang mengalami stunting meningkat resiko untuk menderita infeksi berulang yang dapat mengakibatkan kematian seperti diare, pneumonia dan cacar. Dan juga meningkatkan resiko mengalami penyakit jantung kronik di usia anak. Kegiatan yang  dilakukan dalam pengbdian ini yaitu Focus Group Discussion (FGD). Sasaran kegiatan ialah petugas kesehatan, aparat desa dan tokoh serta masyarakat di wilayah kerja Puskesmas Pamboang Kecamatan Majene Sulawesi Barat. Hasil  kegiatan diperoleh  informasi bahwa petugas kesehatan sudah memahami hal-hal terkait dengan Interprofessional collaboration termasuk factor-faktor yang mempengaruhi baik itu hal yang mendukung maupun yang menghambat sehingga masih terkendala secara teknis dalam  pelaksanaannya Sarannya agar meningkatkan implementasi Interprofessional collaboration maka diperlukan adanya modul teknis pelaksanaan Interprofessional collaboration pada penganggulangan kasus stunting  pada anak di tingkat Puskesmas.